Women in the History of Islamic Education: Roles, Contributions, and Contemporary Challenges - Ridwan, Muhammad; Kamal, Tamrin; Saputra, Riki (El-Rusyd, 2026)
Studies on the role of women in Islamic education have often remained marginalized within the predominantly androcentric narratives of Islamic intellectual history. In fact, since the earliest period of Islam, women have played significant roles as learners, educators, transmitters of knowledge, and drivers of educational institutions. This disparity between historical realities and their academic representation constitutes the background of this study. This research aims to comprehensively examine the roles and contributions of women in the history of Islamic education, identify the various forms of their contributions from historical to contemporary perspectives, and analyze the challenges and opportunities faced by women in the context of Islamic education today. This study employs a qualitative approach using library research. Data were obtained from primary sources, including classical Islamic literature, biographies of female scholars, and works on the history of Islamic education, as well as secondary sources such as academic books, journal articles, and relevant scholarly publications from the last five years. Data collection was conducted through document analysis, while data analysis utilized content analysis and historical–critical analysis, with source triangulation applied to ensure data validity. The findings indicate that women have made significant and sustained contributions to Islamic education in intellectual, pedagogical, institutional, and socio-cultural domains. However, these roles have often been marginalized due to patriarchal social, cultural, and political factors. This study underscores the importance of reconstructing a more inclusive narrative of the history of Islamic education and strengthening gender-just policies and practices that are responsive to contemporary social dynamics.